Epoxy/graphene platelets nanocomposites with two levels of interface strength - Zaman, Izzuddin; Tam, Thanh Phan; Kuan, Hsu-Chiang; Meng, Qingshi; Truc, Bao La; Lee, Luong; Youssf, Osama; Ma, Jun (Elsevier Science Ltd, 2011)
Graphene platelets (GP) are a novel class of nanoﬁllers due to its good compatibility with most polymers, high aspect ratio, high absolute strength and cost-effectiveness. We in this study synthesised two types of epoxy/GP nanocomposites with different interface strength using the combination of sonication and chemical modiﬁcation. Although the surface-modiﬁed graphene platelets (m-GP) formed clusters, a higher degree of dispersion and exfoliation of graphene was observed in each cluster owning to the improved interface by modiﬁcation. The scrolling of graphene was found predominantly in the interface-modiﬁed nanocomposite. At 4 wt%, the modiﬁed nanocomposite shows fracture energy release rate G1c 613.4 J m